2021
DOI: 10.1039/d0ra08287b
|View full text |Cite
|
Sign up to set email alerts
|

A novel green synthesis of silver nanoparticles by the residues of Chinese herbal medicine and their biological activities

Abstract: A novel method for green synthesis of medicinal AgNPs has been developed by using the residues of Chinese herbal medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…The AgNPs in the synthesis condition at pH 2.5 showed the smallest size, although the trend of particle size was increased with a decreasing pH solution from 11 to 3. The nonlinear relationship between pH and the particle size could be similarly observed in the synthesis of AgNPs using herbal extract [54,55]. This could be related to different charged surface on NPs in different pH [55,56].…”
Section: Effect Of the Volume Ratio Of Agno 3 To Rb Solution Onmentioning
confidence: 74%
“…The AgNPs in the synthesis condition at pH 2.5 showed the smallest size, although the trend of particle size was increased with a decreasing pH solution from 11 to 3. The nonlinear relationship between pH and the particle size could be similarly observed in the synthesis of AgNPs using herbal extract [54,55]. This could be related to different charged surface on NPs in different pH [55,56].…”
Section: Effect Of the Volume Ratio Of Agno 3 To Rb Solution Onmentioning
confidence: 74%
“…This Bragg reflection plane corresponds to the face-centered cubic (fcc) phase of silver, as previously reported. 28 The characteristics of the XRD spectrum of the NPs referenced to the JCPDS (Joint Committee on Powder Diffraction Standards -Card No. 05-0667) showed that the material had a crystalline nature.…”
Section: Resultsmentioning
confidence: 99%
“…After 1.0 h of incubation, however, there were not any obvious changes in the color of the mixed solution (Figure S1). As shown in previous studies, , the formation of AgNPs would turn the color of mixed solution to dark brown. This result indicates that the primary extract of Mentha pulegium is helpless for reducing Ag + to Ag 0 within 1.0 h. This may originate from the slow formation rate, which results in very little AgNP generation.…”
Section: Resultsmentioning
confidence: 98%